Multipurpose Smart Assistant - Amutha S, Bhuvaneswari S, Rajes Kannan S, Annapoorani A (International Journal of Control and Automation, 2020)
Voice-pushed era has created awe-inspiring interplay at the complete natural way feasible. With the popularity of speech-driven synthetic wise (AI) assistants like Google domestic, Apple’s Siri, Amazon Echo, the potential to no longer simply listen the query however also recognize and respond in seconds has offered phantasm into fact. A smart Assistant is a software program agent thatcan carry out tasks or services for an person primarily based on verbal instructions. sometimes the time period"chatbot" is used to consult virtual assistants usually or mainly accessed by using on line chat (orin a few cases online chat programs which might be solely for leisure functions). Somevirtual assistants are capable of interpret human speech and respond through synthesized voices. Userscan ask their assistants questions, manipulate domestic automation gadgets and media playback viavoice, and manage different primary obligations inclusive of electronic mail, to-do lists, and calendars withverbal commands. This Multipurpose Smart Assistant functions based on the user commands and serve the user with appropriate services. This Smart Assistant can able to playback a media content from youtube and can able to manage the whatsapp chats by responding to the incoming messages based on the user’s past chat history with a particular sender. This Smart Assistant can control all the electronic appliances and grab information about a particular word from the internet and read it out to the user. It can stream a audio/video content from YouTube.